Experimental investigation during turning process of titanium material for surface roughness. (2021) - Thirumalai, R.; Techato, Kuaanan; Chandrasekaran, M.; Venkatapathy, K.; Seenivasan, M.
Abstract: Manufacturing process is considered to be the most important in all industries to produce finished parts with high accuracy. Almost all industries involving manufacturing processes focus on optimal conditions pertaining to surface quality, production lead time, efficiency and so on. The present work is aimed at demonstrating the application of Taguchi method and Response surface methodology in process parameters optimization. The performance in turning of titanium by using performance investigators such as cutting tool temperature and surface roughness is carried out. This work focusses on the assessment of optimal machining parameters for Titanium material against several cutting tools. Also signal to noise ratio results and analysis are discussed. It is observed from the ANOVA analysis for cutting temperature, that the most influencing cutting parameter in machining the titanium material is cutting speed. The next influencing parameter is the depth of cut. It also observed that the combined parameter feed and depth of cut also contributes to a larger extent in the machining of Titanium material.